Impact of Askling L-PROTOCOL on Biceps Femoris Architecture, Hamstring Flexibility and Sprint Performance - Alonso-Fernandez, Diego; Martinez-Fernandez, Juan; Docampo-Blanco, Pedro; Fernandez-Rodriguez, Rosana (International Journal of Sports Medicine, 2021)
Eccentric training has been shown to be important for hamstring strain injuries rehabilitation and prevention. The Askling L-PROTOCOL (L-P), comprising three exercises aimed at eccentric training and hamstring lengthening, was shown to improve this injuries recovery and relapse times in comparison with other traditional exercise-based protocols. However, the causes of these results remain unclear. This study looks at the impact of an 8-week L-P followed by 4 weeks of detraining on the architecture of the biceps femoris long head, hamstring flexibility and sprint performance. Twenty-eight healthy individuals were divided into two groups: an experimental group, which carried out the L-P, and a control group with no training. Muscle architecture was measured using 2D ultrasound, hamstring flexibility using goniometry and sprint performance using sports radar equipment before (M1) and after (M2) the training period and after detraining (M3). No significant changes were observed between M1 and M2 in the experimental group with regard to fascicle length (t=− 0.79, P>0.05), theoretical maximum speed (t=− 1.43, P>0.05), horizontal force (t=0.09, P>0.05), force application during sprint running (t=− 0.09, P>0.05) and horizontal power (t=− 0.97, P>0.05), but, however, changes were observed in hamstring flexibility (t=− 4.42, d=0.98, P<0.001) returning to pre-training values after detraining period (t=− 1.11, P>0.05). L-P has been shown to be an eccentric protocol of moderate intensity and easy implementation that could be interesting to include throughout a sports season.
Keywords: hamstring strain injury; eccentric training; fascicle length; muscle architecture; ultrasound